Halal Label on Japanese Skincare Product and Its Implication on Indonesian Muslim Consumers’ Buying Decision through Religiosity - Wirawan, Wirawan; Qadrifa, Sabrina Sofi; Migunani, Mitariza (Magister of Communication Science, Sahid University Jakarta., 2022)
This research aims to examine the impact of halal label on buying decision that is mediated by religiosity. Previous studies on these variables did not illustrate consistent findings. Therefore, this research is done to provide more empirical evidence by studying Skin Aqua, a Japanese skincare brand in Indonesia that has recently displayed a halal label on its new packaging. Utilising a survey method, the questionnaires were distributed to 100 respondents selected by using the purposive sampling technique. The path analysis technique was used to examine the hypotheses. The result indicates that halal labels cannot directly bring a significant influence on buying decisions, but religiosity does. Moreover, religiosity may strengthen the impact of halal labels on Indonesian Muslim consumers’ buying decisions, because the effect of Halal Label to Buying Decision is more significant in an indirect manner rather than the direct one.